Reassessing the Stroke Belt: Using small area spatial statistics to identify clusters of high stroke mortality in the US - Karp, David N. (Stroke, 2016)
BACKGROUND AND PURPOSE: The “stroke belt” is described as an 8-state region with high stroke mortality across the southeastern US. Using spatial statistics we identified clusters of high stroke mortality (hot-spots) and adjacent areas of low stroke mortality (cool-spots) for US counties, and evaluated for regional differences in county-level risk factors. METHODS: A cross-sectional study of stroke mortality was conducted using Multiple Cause of Death data (Centers for Disease Control and Prevention) to compute age-adjusted adult stroke mortality rates for US counties. Local indicators of spatial association (LISA) statistics were used for hot-spot mapping. County-level variables were compared between hot- and cool-spots. RESULTS: Between 2008 and 2010 there were 393,121 stroke-related deaths. Median age-adjusted adult stroke mortality was 61.7 per 100,000 persons (IQR=51.4–74.7). We identified 705 hot-spot counties (22.4%), and 234 cool-spot counties (7.5%). 44.5% of hot-spot counties were located outside of the stroke belt. Hot-spots had greater proportions of black residents, higher rates of unemployment, chronic disease, and healthcare utilization, and lower median income and educational attainment. CONCLUSIONS: Clusters of high stroke mortality exist beyond the 8-state stroke belt, and variation exists within the stroke belt. Reconsideration of the stroke belt definition and increased attention to local determinants of health underlying small area regional variability could inform targeted healthcare interventions.